2010
DOI: 10.1186/1753-2000-4-3
|View full text |Cite
|
Sign up to set email alerts
|

Is there a protective effect of normal to high intellectual function on mental health in children with chronic illness?

Abstract: BackgroundHigh intellectual function is considered as a protective factor for children's mental health. Few studies have investigated the effect of intellectual function on mental health in children with chronic illness (CI). The aim of the present study was twofold: First, we asked if normal to high intellectual function (IQ) has a protective effect on mental health in children with CI, and secondly, if this effect is more substantial than in their peers (NCI).MethodsThe participants were selected among child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…However, no study has previously investigated whether intelligence plays the same role in narcolepsy patients. Nevertheless, one study found that narcolepsy patients with a high IQ exhibited significant cognitive impairment, which suggests that intelligence and cognitive impairment are independent 15. When we compared cognitive function and emotional state in patients with different IQ levels in narcoleptics, we found that the high-IQ group performed better in terms of cognitive function and felt less general depressive symptoms.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…However, no study has previously investigated whether intelligence plays the same role in narcolepsy patients. Nevertheless, one study found that narcolepsy patients with a high IQ exhibited significant cognitive impairment, which suggests that intelligence and cognitive impairment are independent 15. When we compared cognitive function and emotional state in patients with different IQ levels in narcoleptics, we found that the high-IQ group performed better in terms of cognitive function and felt less general depressive symptoms.…”
Section: Discussionmentioning
confidence: 76%
“…However, other studies have found contradictory results on this topic. For example, two studies found no difference between narcoleptics and normal controls in terms of visual attention, divided attention to a visual stimulus, and working memory 12,15. These conflicting results may be related to differences in the nature of cognitive tasks, and may be open to diverse interpretations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to allograft function, cognitive and intellectual ability has become an important aspect of success for pediatric recipients. Moreover, high intellectual function, as reflected by childhood intelligence quotient (IQ), has recently been suggested as a protective factor for mental health in children with chronic illness …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, childhood cognitive ability is highly predictive for educational achievement and later occupational outcomes (6) as well as health behavior (7). Furthermore, average to high intelligence is considered to be one of the most important resilience factors for mental health (8,9). Current research indicates that liver transplanted children are at higher risk for developing cognitive deficits compared to the age-matched normal population (10,11).…”
Section: Introductionmentioning
confidence: 99%